Neutrophil and neutrophil extracellular traps in acute kidney injury: from mechanisms to treatments - Fu, Yifei; Wang, Wenjuan; Gong, Na; Zheng, Xumin; Guo, Xinru; Zhuang, Kaiting; Han, Qiuxia; Feng, Zhe; Chen, Xiangmei; Cai, Guangyan (Frontiers in Immunology, 2025)
Immune-inflammatory dysregulation characterizes acute kidney injury (AKI) throughout its early progression and chronic evolution. Neutrophils and the neutrophil extracellular traps (NETs) they release play multiple roles in this process. Recent research indicates that NETs, characterized by their unique “DNA-histone-granule proteins (e.g., neutrophil elastase [NE], myeloperoxidase [MPO], proteinase 3 [PR3], and cathepsin G).” structure, have become a pivotal research focus in neutrophil biology, while their formation is intricately linked to signals within the tissue microenvironment. This review traces neutrophil dynamics from bone marrow development and recruitment to the kidney, culminating in suicidal or vital NETosis. It specifically compares neutrophil extracellular trap (NET) mechanisms in sterile versus infectious AKI. Besides, it details how non-specific NET components, while aiding pathogen and necrotic tissue clearance, simultaneously damage renal tubular epithelial and endothelial cells, amplifying inflammatory cascades. Furthermore, the review comprehensively summarizes therapeutic strategies targeting NETs for AKI, including inhibition of NET formation/release, blockade of specific NET components, and promotion of NET clearance. These studies offer new perspectives on the spatiotemporal-specific roles of NETs in AKI, laying a solid theoretical groundwork for advancing their exploration in AKI subtyping and precision therapy.